2009
DOI: 10.1158/0008-5472.sabcs-09-3049
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Stroma Ratio within the Primary Tumor Is a Prognostic Factor in Early Breast Cancer Patients, Especially in Triple-Negative-Carcinoma Patients.

Abstract: Background: Breast cancer patients comprise a prognostic heterogeneous group. Stroma-tissue surrounding cancer cells plays an important role in tumor behavior. The prognostic value of the tumor-stroma ratio was evaluated.Material and Methods: A cohort of 574 patients with early breast cancer, primarily treated by surgery between 1985 and 1994 was analyzed. The percentage of intra-tumoral stroma was visually estimated on haematoxylin-eosin-stained histological sections from primary tumor tissue by two observers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently Yamashima and colleagues showed that the expression of the other important hallmark of myofibroblasts, a-SMA, correlates with invasive growth and poor clinical prognosis (Yamashita et al, 2010). Likewise, patients with stroma rich-tumors had a shorter relapse-free period and overall survival compared to stroma-poor tumors (de Kruijf et al, 2011). These fi ndings corroborate the previThese findings corroborate the previously shown association between the presence of large number of CAFs and high grade as well as poor prognosis (Cardone et al, 1997).…”
Section: Cafs As Marker Of Patient Prognosismentioning
confidence: 99%
“…Recently Yamashima and colleagues showed that the expression of the other important hallmark of myofibroblasts, a-SMA, correlates with invasive growth and poor clinical prognosis (Yamashita et al, 2010). Likewise, patients with stroma rich-tumors had a shorter relapse-free period and overall survival compared to stroma-poor tumors (de Kruijf et al, 2011). These fi ndings corroborate the previThese findings corroborate the previously shown association between the presence of large number of CAFs and high grade as well as poor prognosis (Cardone et al, 1997).…”
Section: Cafs As Marker Of Patient Prognosismentioning
confidence: 99%
“…In [67] Kruijf et al showed that tumor-stroma ratio is a prognostic factor for relapse-free period. Dekker et.…”
Section: Discussionmentioning
confidence: 99%